Дерматоглифические показатели у девочек-подростков с различными клиническими вариантами вторичной аменореи - Начетова, Т.А. (Фактори експериментальної еволюції організмів, 2014)
Aims. The investigate dermatoglyphic patterns of adolescent girls with of different clinical types of secondary amenorrhea. Methods. In order to find morphogenetic markers of different clinical types of secondary amenorrhea (SA) in adolescent girls, an analysis of dermatoglyphic patterns has been carried out in 102 adolescent girls with SA aged from 13 to 17, who were under clinical research in the S.I. “ICAHC NAMS of Ukraine”; the control group consisted of 50 girls of the same age with a regular menstrual cycle. Results. It has been shown that the clinical types of SA have typical morphogenetic (dermatoglyphic) complexes. Conclusions. The suggested dermatoglyphic complexes can be applied for the prediction of SA in girls.

Key words: dermatoglyphic patterns, adolescent girls, secondary amenorrhea.